Creative Economy Development and Digitalization of MSMEs in Made Village, Surabaya - Panjaitan, Ade Rizky; Akbar, Ahmad Taufik; Maharani, Ida Ayu Putu Savitri Dewi; Shafira, Jihan; Pujiarto, Trimono (Edumedia Solution, 2025)
This community service article titled